Analysis of Factors Affecting the Performance of Stock Funds and Timing and Selection Ability of Fund Managers ---The case of China. - HE, TIANTIAN (2019)
As an important investment tool of modern finance, the fund provides investment opportunities and investment channels for individual investors, it also plays a role in prospering and stabilizing financial markets.